Transcriptomic profiling of the salt-stress response in the halophyte Halogeton glomeratus - Wang, Juncheng (BMC Genomics, 2015)
BACKGROUND: Halogeton glomeratus (H. glomeratus) is an extreme halophyte that is widely distributed in arid regions, including foothills, the Gobi desert of northwest China, and the marginal loess of Central Asia. However, research on the salt-tolerant mechanisms and genes of this species are limited because of a lack of genomic sequences. In the present study, the transcriptome of H. glomeratus was analyzed using next-generation sequencing technology to identify genes involved in salt tolerance and better understand mechanisms of salt response in the halophyte H. glomeratus. RESULTS: Illumina RNA-sequencing was performed in five sequencing libraries that were prepared from samples treated with 200 mM NaCl for 6, 12, 24, and 72 h and a control sample to investigate changes in the H. glomeratus transcriptome in response to salt stress. The de novo assembly of five transcriptomes identified 50,267 transcripts. Among these transcripts, 31,496 (62.66%) were annotated, including 44 Gene Ontology (GO) terms and 128 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Compared with transcriptomes from the control and NaCl-treated samples, there were 2,223, 5,643, 7,510 and 10,908 genes that were differentially expressed after exposure to NaCl for 6, 12, 24, and 72 h, respectively. One hundred and eighteen salt-induced genes were common to at least two stages of salt stress, and 291 up-regulated genes were common to various stages of salt stress. Numerous genes that are related to ion transport, reactive oxygen species scavenging, energy metabolism, hormone-response pathways, and responses to biotic and abiotic stress appear to play a significant role in adaptation to salinity conditions in this species. The detection of expression patterns of 18 salt-induced genes by quantitative real-time polymerase chain reaction were basically consistent with their changes in transcript abundance determined by RNA sequencing. CONCLUSIONS: Our findings provide a genomic sequence resource for functional genetic assignments of an extreme halophyte, H. glomeratus. We believe that the transcriptome datasets will help elucidate the genetic basis of this species’ response to a salt environment and develop stress-tolerant crops based on favorable wild genetic resources. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1373-z) contains supplementary material, which is available to authorized users.